THE ROLE OF SOCIAL MEDIA AS A MEANS OF TOURISM PROMOTION IN NORTH SUMATRA PROVINCE - H Silaban, Pantas; Nainggolan, Arlinton; Sinaga, Remina; Maria Gultom, Priska; Simamora, Hamonangan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
This study aims to determine the forms of promotion on social media of the Tourism Office as a means of increasing tourists, to find out the obstacles experienced by the North Sumatra Province Tourism Office in promoting tourism in North Sumatra Province, to find out the success rate of the Tourism Office in promoting tourism in Sumatra Province. North by using social media. This research is an exploratory research, namely research conducted to explore data and information on new topics or issues aimed at deepening or further research. The purpose of the research is to formulate more accurate questions that will be answered in further research or later research. The results of the research found by researchers are forms of promotion in the form of advertising, sale promotion, publicity, promotion through social media. Promotion through social media creates trust for consumers because there are many testimonials and comments that are useful for users to find out more information. The level of success, seen from the large number of tourists who come and can be seen from how much enthusiasm is given by the community, or how much impression is left by the community on the social media network, the success rate of promotion using social media was successful. Promotion through social media creates trust for consumers because there are many testimonials and comments that are useful for users to find out more information. The level of success, seen from the large number of tourists who come and can be seen from how much enthusiasm is given by the community, or how much impression is left by the community on the social media network, the success rate of promotion using social media was successful. Promotion through social media creates trust for consumers because there are many testimonials and comments that are useful for users to find out more information. The level of success, seen from the large number of tourists who come and can be seen from how much enthusiasm is given by the community, or how much impression is left by the community on the social media network, the success rate of promotion using social media was successful.